Applied shape optimization for fluids - Mohammadi, B.; Pironneau, Olivier (Oxford : Oxford University Press, 2010)
Examining shape optimization problems for fluids, with the equations needed for their understanding and the simulation of these problems, this text introduces automatic differentiation approximate gradients, and automatic mesh refinement.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Structural optimization; Fluid-structure interaction; Fluid dynamics -- Computer programs